Prevalence of iron deficiency anemia and iron deficiency in a pediatric population with inflammatory bowel disease - Carvalho, Fábia Susana Ginja de (2017)
OBJECTIVES: Iron deficiency is the most common cause of anemia in children with inflammatory bowel disease, although the real prevalence is unknown. Intravenous iron is suggested as the first line treatment. This study aims to determine the prevalence of iron deficiency anemia in children with inflammatory bowel disease followed in a Pediatric Gastroenterology Unit of a tertiary center and to evaluate this unit's experience with intravenous iron. MATERIALS AND METHODS: A retrospective cohort study was designed involving children with inflammatory bowel disease followed in that unit between January 2001 and April 2016. Laboratory results were collected at the moment of diagnosis, after one-year follow-up and prior each IV iron administration performed during the study period. Anemia was defined according to World Health Organization criteria and the iron deficiency was defined using recent guidelines. RESULTS: Were studied 69 patients 71% had CD and 29% UC. 50.7% were female. Mean patient age at diagnosis was 13.3 years (range 1--17 years). Prevalence of ID and IDA at diagnosis was 76.8% and 43.5%, respectively. After one year follow-up, those values decreased to 68.1% (p=.182) and 21.7% (p=.002), respectively. Hemoglobin significantly increased (p<.001). Intravenous iron was administered to 92.8% of patients. No adverse reactions were reported. CONCLUSIONS: Intravenous iron is the first line in the treatment of Iron deficiency anemia in Inflammatory Bowel disease and it is safe and effective. Persistent anemia and iron deficiency are common.